2022
DOI: 10.3390/cancers14246085
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on the Impact of the COVID-19 Pandemic on Cutaneous Melanoma Diagnosis in Europe

Abstract: The COVID-19 pandemic has been the epicenter of healthcare attention globally for the past two years, and large-scale adaptations in healthcare provision have been required. This study aimed to investigate the impact of the pandemic and the resulting lockdowns on cutaneous melanoma diagnosis and tumor burdens in Europe. A relevant literature search in electronic databases was conducted from inception to September 2022. The inclusion criteria were: controlled studies published in a peer-reviewed journal evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…It is also worth mentioning that the WALANT approach during the Coronavirus pandemic was recommended by the British Association of Plastic Reconstructive and Aesthetic Surgeons and the British Society for Surgery of the Hand for hand injury management, so that medical resources are conserved [ 29 ]. Expecting a surge of surgical cases following the tremendous impact of the early pandemic phase on skin cancer, WALANT seems a viable, reliable and worthwhile procedure [ 30 , 31 ]. Although we have not performed a formal cost-analysis, we estimate lower total costs in the WALANT group due to the significantly shorter operation theater occupation time and the avoidance of the main operating room, the anesthesiologist and most of the non-medical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning that the WALANT approach during the Coronavirus pandemic was recommended by the British Association of Plastic Reconstructive and Aesthetic Surgeons and the British Society for Surgery of the Hand for hand injury management, so that medical resources are conserved [ 29 ]. Expecting a surge of surgical cases following the tremendous impact of the early pandemic phase on skin cancer, WALANT seems a viable, reliable and worthwhile procedure [ 30 , 31 ]. Although we have not performed a formal cost-analysis, we estimate lower total costs in the WALANT group due to the significantly shorter operation theater occupation time and the avoidance of the main operating room, the anesthesiologist and most of the non-medical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recent COVID-19 pandemic, and the subsequent restrictions to healthcare services, had a profound impact on skin cancer diagnosis and treatment [40,41]. Indeed, an increased incidence of SCC and more complicated methods of reconstruction following NMSC excision, as well as higher melanoma burden and disease progression were revealed [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recent COVID-19 pandemic, and the subsequent restrictions to healthcare services, had a profound impact on skin cancer diagnosis and treatment [40,41]. Indeed, an increased incidence of SCC and more complicated methods of reconstruction following NMSC excision, as well as higher melanoma burden and disease progression were revealed [40,41]. Considering the association between delay of surgery and increased mortality recently revealed, and the heavy workload of NMSC cases anticipated in the postpandemic era, the timely and adequate treatment provided is of utmost importance [42].…”
Section: Discussionmentioning
confidence: 99%
“…This point deserves special attention, as the COVID-19 pandemic has been the central global emergency during the past 2 years, resulting in large-scale adaptations in healthcare provisions. A recent meta-analysis by Seretis et al [ 35 ] investigated the relationship of the pandemic outbreak and lockdowns with melanoma diagnoses and related burdens across Europe. Through an extensive literature search, the authors selected 25 studies involving 32,231 patients and found significantly increased mean Breslow thickness, ulceration rates, and resultant tumor staging in the post-COVID era, indicating that the pandemic caused a heavier tumor burden and faster disease progression state due to healthcare adaptations, especially during the earlier pandemic waves.…”
Section: Discussionmentioning
confidence: 99%